Experimental investigations of interaction of supercritical electron beams with plasma - Chupikov, P.T.; Medvedev, D.V.; Onishchenko, I.N.; Panasenko, B.D.; Prokopenko, Yu.V.; Pushkarev, S.S.; Faehl, R.J.; Yegorov, A.M. (Вопросы атомной науки и техники, 2002)
The first section of the collective ions acceleration based on simultaneous temporal and spatial modulation of relativistic electron beam (REB) was studied experimentally. The virtual cathode was originated in the electrodynamic structure consisting of two tubes with different diameters (jump of electrodynamics) by REB, produced in magnetically insulated diode. At plasma assistance the low-frequency oscillations of REB current and the low-frequency microwave radiation were obtained due to the virtual cathode periodical relaxation in the processes of charge compensation by ionized residual gas.